The GAPVU cash transfer program in Mozambique: an assessment - Datt, Gaurav; Payongayong, Ellen; Garrett, James L.; Ruel, Marie T. (International Food Policy Research Institute, 1997)
The GAPVU cash transfer program is an important safety net for urban Mozambique. The coverage of the program is impressive within the urban sector, reaching about 16 percent of all urban households. Although the mean transfer amount is just over a dollar per capita per month, it still represents about 13 percent of the beneficiaries' per capita consumption. Despite limited enforcement of means testing, nearly two-thirds of the beneficiary population are deemed to be absolutely poor by a modest poverty line. Net of GAPVU transfers, the proportion in poverty would have been above 70 percent. Limited evidence on nutritional and other nonconsumption indicators is suggestive of the GAPVU beneficiary households being more deprived than urban households in general. GAPVU transfer benefits are progressive among the beneficiary households, and are not confined to those near the poverty line.